Australia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
The first part of the study investigates Australia's recent growth and productivity performance and then analyzes the impact of structural reforms on productivity growth. The short- and long-term effects of structural reforms on productivity growth are estimated using pooled and fixed effect distributed lag models. The study also includes the following statistical data: labor market, selected price index, selected fiscal indicators, credit aggregates, money supply, banking soundness statistics, current account, exports and imports, exports by commodity group, direction of trade, capital and financial account, interest rates, and so on.